2008
DOI: 10.1007/s00213-008-1089-8
|View full text |Cite
|
Sign up to set email alerts
|

Protracted time-dependent increases in cocaine-seeking behavior during cocaine withdrawal in female relative to male rats

Abstract: The effects of reproductive cycle and withdrawal duration on cocaine-seeking behavior are additive and time-dependent increases in cocaine-seeking behavior are more enduring in females than in male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
129
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 66 publications
(98 reference statements)
20
129
3
Order By: Relevance
“…Our finding that E 2 treatment enhanced extinction of cocaine seeking even in ovariectomized rats that were perseverating for up to 5 wk suggests a potentially vital role for E 2 in the recovery from cocaine abuse. The importance of E 2 is underscored by our finding that female rats in the absence of E 2 failed to suppress cocaine seeking during extinction, and may explain why gonadally intact female rats in estrus (low E 2 levels) are more resistant to extinction of drug seeking than are male rats (Kerstetter et al 2008;Anker et al 2010). Therefore, low E 2 levels may increase the risk of relapse in some women, and this risk may be exacerbated by cocaine-induced menstrual cycle disorders (Mello and Mendelson 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Our finding that E 2 treatment enhanced extinction of cocaine seeking even in ovariectomized rats that were perseverating for up to 5 wk suggests a potentially vital role for E 2 in the recovery from cocaine abuse. The importance of E 2 is underscored by our finding that female rats in the absence of E 2 failed to suppress cocaine seeking during extinction, and may explain why gonadally intact female rats in estrus (low E 2 levels) are more resistant to extinction of drug seeking than are male rats (Kerstetter et al 2008;Anker et al 2010). Therefore, low E 2 levels may increase the risk of relapse in some women, and this risk may be exacerbated by cocaine-induced menstrual cycle disorders (Mello and Mendelson 1997).…”
Section: Discussionmentioning
confidence: 93%
“…In humans, levels of cocaine craving vary across the menstrual cycle (Fox et al 2008) with evidence to suggest that these levels are influenced by the ratio of estradiol to progesterone (Sinha et al 2007). Similar findings have been observed in animal models in which levels of cocaine-seeking vary across the estrous cycle with the highest levels observed during estrus (Kippin et al 2005;Kerstetter et al 2008;Feltenstein and See 2007;Feltenstein et al 2011), a period when there are higher levels of estradiol compared to progesterone (Feltenstein et al 2009). Results have also shown that the incubation effect, the progressive increase in cocaine-seeking over protracted abstinence (Grimm et al 2001), is heightened and prolonged in estrus females compared to males and to females in non-estrus phases (Kersetter et al 2008).…”
Section: Dose-dependent Efficacy Of Exercise To Attenuate Cocaine-seesupporting
confidence: 80%
“…Consistent with findings in humans, the enhanced biological vulnerability seen in female laboratory animals is believed to be mediated by ovarian hormones, particularly estrogen which has been shown to increase vulnerability at each of the phases of the addiction process (Kerstetter et al 2008;Lynch 2006;Roth and Carroll 2004;Larson et al 2007). Although females in all phases of their estrous cycle exhibit incubation of cocaine craving (Kerstetter et al 2008), females tested during estrus (defined as high levels of estrogen relative to progresterone; Feltenstein et al 2009) maintain a potentiation in cocaine-seeking longer than those in other phases (Kippin et al 2005;Feltenstein and See 2007;Kersetter et al 2008).…”
Section: Animal Models Of Cocaine Addiction and Relapsesupporting
confidence: 57%
See 2 more Smart Citations